2016
DOI: 10.1128/ecosalplus.esp-0006-2016
|View full text |Cite
|
Sign up to set email alerts
|

Animal EnterotoxigenicEscherichia coli

Abstract: Enterotoxigenic Escherichia coli (ETEC) is the most common cause of E. coli diarrhea in farm animals. ETEC are characterized by the ability to produce two types of virulence factors; adhesins that promote binding to specific enterocyte receptors for intestinal colonization and enterotoxins responsible for fluid secretion. The best-characterized adhesins are expressed in the context of fimbriae, such as the F4 (also designated K88), F5 (K99), F6 (987P), F17 and F18 fimbriae. Once established in the animal small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(238 citation statements)
references
References 605 publications
(512 reference statements)
4
201
0
Order By: Relevance
“…Other studies have reported a high prevalence of C. difficile toxins in healthy animals concluding no clear relationship between diarrheal outbreaks and the detection of toxigenic C. difficile in pigs (Yaeger et al, 2007;Álvarez-Pérez et al, 2009). ETEC has been and still is considered the main agent responsible for intestinal disorders in neonatal piglets being F4, F5, F6 and F41, the main fimbriae associated with diarrhea, (Dubreuil et al, 2016;Luppi et al, 2016). In the present study, ETEC strains were infrequently isolated from both diarrheic and non-diarrheic piglets, similar to the results reported previously by others (Kongsted et al, 2013;Kongsted et al, 2018;Larsson et al, 2015;Mesonero-Escuredo et al, 2018).…”
Section: Fig 2 (Continued)supporting
confidence: 91%
“…Other studies have reported a high prevalence of C. difficile toxins in healthy animals concluding no clear relationship between diarrheal outbreaks and the detection of toxigenic C. difficile in pigs (Yaeger et al, 2007;Álvarez-Pérez et al, 2009). ETEC has been and still is considered the main agent responsible for intestinal disorders in neonatal piglets being F4, F5, F6 and F41, the main fimbriae associated with diarrhea, (Dubreuil et al, 2016;Luppi et al, 2016). In the present study, ETEC strains were infrequently isolated from both diarrheic and non-diarrheic piglets, similar to the results reported previously by others (Kongsted et al, 2013;Kongsted et al, 2018;Larsson et al, 2015;Mesonero-Escuredo et al, 2018).…”
Section: Fig 2 (Continued)supporting
confidence: 91%
“…2). It has been widely reported in the scientific literature that ETEC challenge in pigs was not associated with significant macroscopic lesions or morphological changes in the intestinal mucosa resulting from the toxic activity of ETEC enterotoxins [57,61,62]. However, other studies have reported that the necropsy of challenged pigs with ETEC or naturally infected animals, has revealed several lesions such as; dehydration, dilation of the stomach and the small intestines, gastric infarcts in the mucosa of the stomach, and congestion of the mucosa of both the small intestine and the colon [57,63].…”
Section: Determining Factorsmentioning
confidence: 99%
“…Tab1 showed detailed information on the primers used for screening for virulence genes [2,5,7,9,11,17,31] . 30 isolate strains same as from 2.5 for PCR assay.…”
Section: Classification Of Virulence Genes Using Pcr Assaysmentioning
confidence: 99%
“…Evidence suggests that specific serotype of E.coli is among the most important factors for enteric disease and sepsis [2][3][4] . The resulting problems of livestock and poultry deaths, antibiotic residues and the spread of drug resistance become a growing public health concern worldwide.…”
Section: Introductionsmentioning
confidence: 99%